2020
DOI: 10.1088/1361-6595/aba2ac
|View full text |Cite
|
Sign up to set email alerts
|

Water and xenon ECR ion thruster—comparison in global model and experiment

Abstract: Gridded ion thrusters are one of the most commonly used types of electric propulsion, and alternative propellants have been studied for miniature ion thrusters to meet the demand of propulsion systems for micro-/nano-satellites. Water is a candidate as an alternative non-pressurized propellant for a CubeSat thruster. It is consistent with the CubeSat concept of short-term and low-cost development. In this paper, the characteristics of a miniature water ion thruster were compared with those of a xenon one using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In the case of water vapor, on the other hand, the actual ion species and their abundance ratios in the plume have not been known. Instead, in reference to the previous research for a microwave discharge ion source [44], it was reported that OH + , H 3 O + , and O + were mainly observed other than H 2 O + , and their existence were 15 %, 12 %, and 5 % of H 2 O + , respectively. The referenced results, however, are assumed to be derived from different plasma parameters from those of the Hall thruster discharge plasma.…”
Section: Performance Analysis Methodsmentioning
confidence: 88%
“…In the case of water vapor, on the other hand, the actual ion species and their abundance ratios in the plume have not been known. Instead, in reference to the previous research for a microwave discharge ion source [44], it was reported that OH + , H 3 O + , and O + were mainly observed other than H 2 O + , and their existence were 15 %, 12 %, and 5 % of H 2 O + , respectively. The referenced results, however, are assumed to be derived from different plasma parameters from those of the Hall thruster discharge plasma.…”
Section: Performance Analysis Methodsmentioning
confidence: 88%
“…In addition, integrating the discharge model [57] and the plume morphology model [58] into the model system can further improve the approximation introduced in equation ( 5). The NNM can be updated dynamically based on in-orbit test data using transfer-learning methods [59].…”
Section: Resultsmentioning
confidence: 99%
“…Examples include the Beihangkongshi-1 satellite with NPT30-I2 that was injected into a circular, Sun-synchronous orbit [1], the European Space Agency's (ESA) BepiColombo mission to Mercury with the T6 Kaufmann-type thruster [2][3][4], the satellite SJ-9 A with the LIPS-200 ion thruster which carried out an ion electric propulsion system flight test plan [5,6], the gravity field and steady-state ocean circulation explorer (GOCE) mission using the T5 Kaufmann type thruster for drag compensation [7], the Dawn mission and the Deep Space 1 mission with the NASA Solar Technology Application Readiness (NSTAR) ion thruster of the National Aeronautics and Space Administration [8][9][10], the Japanese Aerospace Exploration Agency's Hayabusa sample-return missions with the µ10 thruster to the near-Earth asteroids [11], [12]. Meanwhile, the working mechanism of the ion thruster has also been extensively studied, including the discharge chamber [13][14][15][16] that generates plasma and the optic system [17][18][19][20][21][22] that provides thrust.…”
Section: Introductionmentioning
confidence: 99%